Progressive inner nuclear layer dysfunction in non-optic neuritis eyes in MS. Issue 1 (January 2018) - You, Yuyi; Graham, Elizabeth C.; Shen, Ting; Yiannikas, Con; Parratt, John; Gupta, Vivek; Barton, Joshua; Dwyer, Michael; Barnett, Michael H.; Fraser, Clare L.; Graham, Stuart L.; Klistorner, Alexander
Abstract : Objective: To investigate primary retinal functional changes in non-optic neuritis (ON) eyes of patients with MS by full-field electroretinography (ERG). Methods: Seventy-seven patients with relapsing-remitting MS with no history of clinical ON in at least 1 eye and 30 healthy controls were recruited in the cohort study. Full-field ERGs were recorded, and retinal optical coherence tomography scans were performed to assess the thicknesses of peripapillary retinal nerve fiber layer (RNFL) and retinal ganglion cell layer–inner plexiform layer (GCL-IPL). Annual MRI scans were also carried out to evaluate the disease activity in the brain. Patients were followed up for 3 years. Results: At baseline, a delayed b-wave peak time was observed in the cone response ( p < 0.001), which was associated with the thicknesses of RNFL and GCL-IPL. The peak time of the delayed b-wave also correlated with the Expanded Disability Status Scale, T2 lesion volume, and disease duration. During the 3-year follow-up, progressive ERG amplitude reduction was observed (both a- and b-waves, p < 0.05). There was a correlation between the b-wave amplitude reduction and longitudinal RNFL loss ( p = 0.001). However, no correlation was found between longitudinal ERG changes and disease activity in the brain. Conclusions: This study demonstrated progressive inner nuclear layer dysfunction in MS. The borderline a-wave changes suggested some outer retinal dysfunction as well. The correlation between full-field ERG changes and retinal ganglion cell loss suggested that there might be subclinical retinal pathology in MS affecting both outer and inner retinal layers.